Longitudinal Structure of Oxygen Torus in the Inner Magnetosphere: Simultaneous Observations by Arase and Van Allen Probe A. Issue 19 (10th October 2018) - Nosé, M.; Matsuoka, A.; Kumamoto, A.; Kasahara, Y.; Goldstein, J.; Teramoto, M.; Tsuchiya, F.; Matsuda, S.; Shoji, M.; Imajo, S.; Oimatsu, S.; Yamamoto, K.; et al.
Abstract: Simultaneous observations of the magnetic field and plasma waves made by the Arase and Van Allen Probe A satellites at different magnetic local time (MLT) enable us to deduce the longitudinal structure of an oxygen torus for the first time. During 04:00–07:10 UT on 24 April 2017, Arase flew from L = 6.2 to 2.0 in the morning sector and detected an enhancement of the average plasma mass up to 3.5 amu around L = 4.9–5.2 and MLT = 5.0 hr, implying that the plasma consists of approximately 15% O + ions. Probe A moved outbound from L = 2.0 to 6.2 in the afternoon sector during 04:10–07:30 UT and observed no clear enhancements in the average plasma mass. For this event, the O + density enhancement in the inner magnetosphere (i.e., oxygen torus) does not extend over all MLT but is skewed toward the dawn, being described more precisely as a crescent‐shaped torus or a pinched torus. Plain Language Summary: In the early 1980s, it was discovered that the O + ion density is sometimes enhanced in a limited range of altitude in the deep inner magnetosphere (approximately 10, 000‐km to 30, 000‐km altitude). This O + density enhancement was originally named the oxygen torus, which implies azimuthal symmetry of the density enhancement. However, its longitudinal structure remains poorly known. This study investigates the longitudinal structure of the oxygen torus for the first time using simultaneous observations from the Arase and Van Allen Probe A satellites. We find that the oxygen torus does not extend over all longitudes but is localized to the dawn sector, indicating a crescent‐shaped torus. Key Points: Simultaneous observations by Arase and Van Allen Probe A are used to examine the longitudinal structure of an oxygen torus Only Arase detected an enhancement of the average plasma mass up to 3.5 amu around L = 4.9‐5.2 and MLT = 5.0 hr For this event, the longitudinal extent of the O + density enhancement is better described as a crescent‐shaped torus or a pinched torus